The Search for the Convergence of the Absolute Beginning and the Doctrine of Creatio ex Nihilo - Fedor MINAKOV (Богословські роздуми: Східноєвропейський журнал богословʼя)
Science and theology have very different methodology and use different tools. Despite the differences sometimes both disciplines try to answer same question. One of the questions addressed by science and theology is the origin of the universe. Present article is an attempt to describe how certain scientific achievements in cosmology can support biblical message about the beginning of the world. Bible teaches that the world was created by God out of nothing a finite time ago. Current cosmology holds to the view that is widely known as the Big Bang theory. According to this theory the universe appeared out of the state of infinite density around 15 billion years ago. This revolutionary statement implies that modern physicists do not adhere anymore to the view that the universe is eternal. Thus, both Bible and science claim that the universe had the beginning. Some theoretical physicists have proposed that the universe came out of nothing. Analysis shows that although the statement sounds similar to the doctrine of creatio ex nihilo it has different meaning. However, this difference does not annul the possibility of the convergence of two sides.